Artificial Intelligence in Foreign Language Education: Transforming Teaching and Learning - Mudra, Olena; Tonenchuk, Tetiana; Danylovych, Oksana (Видавничий дім «Гельветика», 2025)
The integration of Artificial Intelligence (AI) in foreign language education has redefined traditional instructional paradigms by introducing adaptive, interactive, and personalized learning mechanisms. AI-driven educational technologies, including Intelligent Tutoring Systems (ITS), Natural Language Processing (NLP) applications, and adaptive learning platforms, contribute to individualized instruction, real-time feedback, and flexible learning environments. ITS, exemplified by systems such as Duolingo and Rosetta Stone, dynamically modify content based on learner progress, fostering an adaptive learning trajectory. NLP-based applications, such as Grammarly and Babbel, facilitate linguistic competence by offering grammar correction, pronunciation assessment, and AI-powered conversational agents for interactive language practice. Additionally, personalized learning platforms like Knewton and Lingvist employ performance analytics to tailor instructional pathways, thereby promoting self-directed learning and increasing learner engagement. Despite the pedagogical advancements afforded by AI, several challenges persist, including concerns regarding data privacy, potential over-reliance on automation, and unequal access to technology. Addressing these limitations necessitates a balanced approach that integrates human interaction with AI-enhanced methodologies to maintain educational equity and effectiveness. This article examines the pedagogical implications, benefits, and constraints associated with AI in language education, underscoring the importance of ethical AI deployment, adherence to regulatory frameworks, and continuous technological refinement. Future research should prioritize the optimization of adaptive learning models and the reduction of accessibility disparities to maximize AI’s transformative potential in foreign language instruction.
Keywords: Artificial Intelligence; Language Learning; Intelligent Tutoring Systems; Personalized Learning; Educational Technology; AI in Education